Effects of forced displacement on access to education in Colombia (2020)
The armed conflict in Colombia brought with it different types of human rights violations, including the forced displacement of millions of people. One of the most recurrent causes of conflict is the increase in poverty, promoted by low educational levels. This research seeks to know the behavior of access to different levels of schooling, forcibly displaced people. The methodology is based on an exploration of the main indicators on education, taken from the Open Data Portal of the Colombian government, together with a normative analysis that allows to identify the evolution of the public policy on displacement, it was found that the primary level accesses the 8 %, at the secondary level 5% and at the level of higher education, no more than 2% of people are admitted in conditions of forced internal displacement. It is concluded that, since only 15% of the displaced persons access formal education, there is a great vulnerability of these population groups, which prolongs intergenerational poverty, increasing the possibilities of generating social unrest.